2021
DOI: 10.1016/j.anr.2021.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Responses of Pregnant Women to the Early Stage of COVID-19 Pandemic in the Network Era in China: Online Questionnaire Study

Abstract: Purpose The aim of the present study was to examine the behavioral responses of pregnant women during the early stage of Coronavirus Disease 2019 (COVID-19) outbreak. Methods We recruited 1,099 women to complete an online questionnaire survey from February 10 to February 25, 2020. The subjects were divided into two groups (the pregnant women group and the control group). Results Concerns about infection: most of the participants watched the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…This might be because the present study was conducted in the "8 th wave" of the COVID-19 pandemic, just before the disease became a category 5 infectious disease and the threat of infection eased. In addition, 30.6% of pregnant women continued to exercise at home compared with 8% of non-pregnant women in the early stages of the COVID-19 pandemic [32]. In the present study, 35.0% of the participants exercised at home, a percentage similar to that reported in a previous study.…”
Section: Discussionsupporting
confidence: 87%
“…This might be because the present study was conducted in the "8 th wave" of the COVID-19 pandemic, just before the disease became a category 5 infectious disease and the threat of infection eased. In addition, 30.6% of pregnant women continued to exercise at home compared with 8% of non-pregnant women in the early stages of the COVID-19 pandemic [32]. In the present study, 35.0% of the participants exercised at home, a percentage similar to that reported in a previous study.…”
Section: Discussionsupporting
confidence: 87%
“…A reduction of physical activity during the pandemic in pregnant women (regardless of the trimester) was also noted in studies by Hashim et al [ 58 ]—of all surveyed women, 53.6% reduced time spent on physical activity and only 13.8% increased it. In turn, Hu et al [ 59 ] showed that during the early stage of the pandemic, more nonpregnant women reduced their physical activity compared to pregnant women (50.0% vs 40.4%). Nascimento el al.…”
Section: Discussionmentioning
confidence: 99%
“…When stratifying across the PA intensity, one study among postmenopausal women had lower levels of PA (68), three other studies reported low MVPA among adults with or without the chronic disease (66) and COVID-19 patients (62,75), and one study reported a decrease in LMVPA among adults with or without the chronic disease (127). On the other hand, eight studies have reported total PA level has increased during the pandemic among diabetes patients (48,105,132), adults with or without the chronic disease (82,117), overweight and obese (89), outpatients (95), and pregnant women (57). One study among adults with chronic diseases engaged in higher LMVPA due to the fear of getting COVID-19 (24).…”
Section: Physical Activity Among Adults With Special Considerations A...mentioning
confidence: 99%